MIDDLE-EAST HUMANITARIAN CRISIS : A NEED FOR UNITED NATIONS PEACE-BUILDING ENFORCEMENTS - Adewumi, Tayewo (Khairun Law Journal, 2025)
The State of Israel has been in the midst of armed conflicts for many decades with Palestines Hamas while Lebanonas Hezbollah and Yemens Houthi have been involved in solidarity conflict. The fresh conflicts began in October 7, 2023 when Hamas launched an unprecedented attack on Israel which took the lives of over 1000 Israelis. The conflicts have intensified with the Hezbollah and Houthi attacking Israel. Israel had carried out attacks on Lebanon and Yemen in retaliation. This ongoing conflict has greatly affected these countries stability, peace, and security, threatening further humanitarian crises. This article discusses the source of the conflict, the current situation of the conflict, and ways to resolve the conflict. In discussing the above, this article adopts a theoretical and doctrinal study of primary and secondary sources as contained in the United Nations Charter, international treaties, conventions and protocols, journal articles, books, newspapers, and materials sourced from the internet.  The article argues that though, the United Nations General Assembly in September 2024 resolved that Israel should vacate Palestinian territory, there is a need for peace-building intervention and enforcement by the United Nations to forestall further humanitarian crises in the Middle East.